The Correlation Status of the Old Ukrainian Language and the Linguistic and Ethnical (National) Consciousness in ХIV–ХVII cc. (Linguostylistic Studies, 2015)
The research focuses on the correlation between public status of the Old Ukrainian language in diachrony (14–17 cc.) and different displays of linguistic and ethnical (national) consciousness in the context of multilingualism and non-state status of Ukraine. In the article, it is revealed the evolution of theoretical interpretation of lingual and ethnical relations in the works of Ukrainian, European and American researchers and it is formalized two basic theories: nation and language as a socio-economic category and nation and language as an ethnic-political category.The analyzed social reality proved at least three displays of linguistic and ethnical consciousness under conditions of multilingualism and non-statehood: linguistic and ethnical divergence (when ethnic awareness of oneself as Ukrainian did not mean to use Old Ukrainian publicly), partial linguistic and ethnical convergence (when ethnic awareness of oneself as Ukrainian determined to use partially the Old Ukrainian language in the public sphere), and full linguistic and ethnical convergence, where ethnicity and language coincided which was a rare phenomenon at that time – and it could be interpreted as a high level of linguistic and ethnical or national consciousness.Such condition of linguistic and ethnical consciousness was a result of that time predominant political ideologeme of the Ukrainian space: gente Ruthenus, natione Polonus – so called double standard of self identification according to ethnic origin and nationality. Finally, it caused complicated and delayed till now method of formation of Ukrainian nation and statehood unlike Polish or Check and other West European linguistic and ethnic (national) societies. Key words: diachrony, linguistic and ethnical consciousness, linguistic and ethnical divergence, partial linguistic and ethnical convergence, full linguistic and ethnical convergence. References